PENGUATAN KETERAMPILAN BERBAHASA INGGRIS TNI AU SATRAD 212 RANAI KABUPATEN NATUNA - Hikmaharyanti, Putu Desi Anggerina; Deni Ariyaningsih, Ni Nyoman; Sri Rwa Jayantini, I Gusti Agung; Verayanti Utami, Ni Made (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service program aims to facilitate the improvement of English skills for military personnel of Radar Unit 212, Indonesian Air Force, in Natuna Regency. This area is in close proximity to the South China Sea, which is still subject to territorial disputes among several Southeast Asian countries. As an international language, English plays a crucial role as a communication bridge for Air Force personnel. By implementing Communicative Language Teaching (CLT), a teaching method focusing on actual interaction such as conversation and discussion, the Air Force personnel can benefit from this English skills improvement program.